Ordinary Credit Units, Benefit with Salary Scale, and Projecting Credit Units - Susanto, Sunarta (Operations Research: International Conference Series, 2020)
In determining the benefits of a pension fund, proper calculations are needed so as not to provide a pension that is too small or too large for someone. The importance of discussing the problems in pension funds is to understand the various problems that exist in determining pension funds. The purpose of making the solution to the selected questions is because the author feels that a discussion about these questions is needed. The problems that exist are sought to be solved using the Traditional Unit Credit (TUC) method and the Projected Unit Credit (PUC) method. The result obtained from the problem under discussion is that if only changes in the age part are entered, it means that it is only necessary to multiply the previously obtained normal cost by the difference from the age in the specified year with the entered age. For those who survive, the normal fee is IDR 33,125, if there are 92 participants who are still alive, the normal fee is IDR. 3,047,490, if there are 96 participants who are still alive, the normal fee is IDR 3,180,000, and if all participants are still alive, the normal fee is IDR 3,312,510. It is hoped that the discussion of the selected questions will help readers understand how to solve problems in determining pension funds.